2016
DOI: 10.1016/j.mgene.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin knockdown strongly affects cotton boll weevil egg viability but not the number of eggs laid by females

Abstract: Vitellogenin (Vg), a yolk protein precursor, is the primary egg nutrient source involved in insect reproduction and embryo development. The Cotton Boll weevil (CBW) Anthonomus grandis Boheman, the most important cotton pest in Americas, accumulates large amounts of Vg during reproduction. However, the precise role of this protein during embryo development in this insect remains unknown. Herein, we investigated the effects of vitellogenin (AgraVg) knockdown on the egg-laying and egg viability in A. grandis fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
5
24
1
Order By: Relevance
“…Moreover, the existence of some other remarkable characteristics such as conserved GL/ICG motifs and cysteine residues are similar to those that exist in other insect Vgs, including the lepidopterans [21,23,28,47,53,63,68]. In the CcVg protein sequence, the DGQR was positioned at 13 residues upstream of the GI/LCG motif that is conserved in almost all lepidopteran Vgs [47,64].…”
Section: Plos Onementioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, the existence of some other remarkable characteristics such as conserved GL/ICG motifs and cysteine residues are similar to those that exist in other insect Vgs, including the lepidopterans [21,23,28,47,53,63,68]. In the CcVg protein sequence, the DGQR was positioned at 13 residues upstream of the GI/LCG motif that is conserved in almost all lepidopteran Vgs [47,64].…”
Section: Plos Onementioning
confidence: 78%
“…The dsRNA was formed. The MEGAscript 1 RNAi kit has been successfully used in several RNAi experiments [52][53][54]. A reaction of dsRNA (20 μL) was set in a standard PCR tube.…”
Section: Plos Onementioning
confidence: 99%
“…Double-stranded RNA (dsRNA) is the RNAi trigger molecule that primes the post-transcriptional downregulation of a target gene [ 22 24 ]. Studies using this technology showed efficient silencing of several target genes through microinjection into larvae and adult CBW insects [ 1 , 25 , 26 ], whereas experiments involving the dsRNA oral uptake resulted in ineffective gene knockdown [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of dsRNA can be achieved by soaking, microinjection or feeding, and the RNAi signal is subsequently transported between cells and tissues [ 40 ]. In CBW, the dsRNA microinjection methodology is known to work well [ 1 , 25 , 26 ], while oral feeding is not so effective [ 18 ], and soaking methodology has not been tested. The oral ingestion of dsRNA is associated with some barriers, such as the exposure of the dsRNA to nucleases secreted in the gut juice, the gut pH, the dsRNA concentration and dsRNA resistance [ 38 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of RNAi-based technologies for the management of insect pests provides new tools for crop protection that can be highly species-specific and environmentally friendly. Genes that are essential for insect survival, fecundity and/or development have been proposed as good RNAi targets to be applied in the control of agricultural pests and vectors of diseases ( Bally et al, 2016 ; Coelho et al, 2016 ; Murphy et al, 2016 ; Macedo et al, 2017 ; Niu et al, 2017 ; Knorr et al, 2018 ; Lopez et al, 2019 ). We observed that disruption of cuticle tanning metabolic pathway by suppression of AgraLac2 transcripts caused severe morphological deformations in A. grandis and negatively affected insect development and molting, inducing high mortality rates.…”
Section: Discussionmentioning
confidence: 99%